The Comparison of Engineering Properties Between Single and Double Layer Porous Asphalt made of Packing Gradation - Hardiman M. Y (Institute of Research and Community Outreach - Petra Christian University, 2008)
is paper presents the comparison of engineering properties between single and double layer porous asphalt (SLPA and DLPA) made of packing gradation. Three nominal maximum aggregate sizes (NMAS) were tested each made up of 10, 14, and 20 mm for SLPA. While for the DLPA with 30, 20, and 15 mm top layer are made of 10 and 14 mm NMAS, with a base layer of 20 mm NMAS. Total thickness of all mixes is 70 mm. Binders used are 60/70 penetration base bitumen and polymer binder styrene-butadiene-styrene (SBS). The result shows that the properties of SLPA mix namely permeability and resistance to abrasion loss decreases when the NMAS in SLPA decreases. The abrasion loss of DLPA mixes increases when the porous asphalt top layer thickness decreases, while drainage time value decreases. However, SLPA with 20 mm NMAS exhibits higher abrasion loss compared to all DLPA mixes.